1993
DOI: 10.1002/chir.530050703
|View full text |Cite
|
Sign up to set email alerts
|

Rac‐Flurbiprofen is more ulcerogenic than its (S)‐enantiomer

Abstract: The most common, and sometimes life-threatening, side-effects associated with the human use of the analgesic, nonsteroidal antiinflammatory drugs (NSAIDs) are gastrointestinal. These include gastritis, ulceration, and severe bleeding. The aryl propionic acid class of NSAIDs are among the most widely used of these drugs in the world, including rac-ibuprofen, rac-flurbiprofen, and rac-ketoprofen. Marketed as racemates, it was assumed that the "inactive" (R)-enantiomers, having no cyclooxygenase inhibiting effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 8 publications
(2 reference statements)
3
32
1
1
Order By: Relevance
“…[69][70][71] The majority of ibuprofen formulations on the market contain a racemic mixture of dexibuprofen [(+)-ibuprofen] and (À)-ibuprofen. Studies have shown that R-(À)-ibuprofen can be converted to S-(+)-ibuprofen in the body after oral administration.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
“…[69][70][71] The majority of ibuprofen formulations on the market contain a racemic mixture of dexibuprofen [(+)-ibuprofen] and (À)-ibuprofen. Studies have shown that R-(À)-ibuprofen can be converted to S-(+)-ibuprofen in the body after oral administration.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
“…The data also suggest that (S)-flurbiprofen could be used to inhibit inflammation and pain in intensive inflammation, while the (R)-enantiomer could be used for the treatment of pain only. Since (R)-flurbiprofen caused less toxicity in rats than the (S)-enantiomer or the racemic compound [1,42], a reduction of gastrointestinal tract side effects might be achieved by employing (R)-flurbiprofen in pain therapy. There is, however, a need to compare the effectiveness and side effects of flurbiprofen enantiomers in patients suffering from different types of painful diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The substrate enantiomeric excess, for the Candida rugosa lipase catalyzed reaction at 96 hours and at water activity of 0.65, in n-heptane, isooctane, and n-nonane was found to be 40.9, 93.0, and 50.0 , respectively 77 . The S-enantiomer of flurbiprofen 2-fluoro-a-methyl-1,1 -biphenyl -4-acetic acid possesses most of its antiinflammatory action, but the presence of the R-enantiomer is reported to greatly enhance its gastrointestinal toxicity 107 . A later study reported that R-flurbiprofen is less potent as an analgesic than S-flurbiprofen, but it caused little toxicity in comparison to its antipode 108 .…”
Section: Synthesis Of Various Enantiomers By Using Lipasesmentioning
confidence: 99%
“…Single enantiomers are more important than their racemic form, because some enantiomers in their racemic form are toxic. For example the S-enantiomer of flurbiprofen 2-fluoro-a-methyl-1,1 -biphenyl -4-acetic acid possesses most of its anti-inflammatory action but, if R-enantiomer is also present then it greatly enhances its gastrointestinal toxicity 107 .…”
Section: Advantages Of Enantiomersmentioning
confidence: 99%